2017
DOI: 10.1002/cam4.1118
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the American Joint Commission on Cancer (8th edition) changes for patients with stage III gastric cancer: survival analysis of a large series from a Specialized Eastern Center

Abstract: The 8th edition of the TNM was released in 2016 and included major revisions, especially for stage III. We aimed to compare the prognostic value of the 7th and 8th editions of the AJCC TNM classification for stage III gastric cancer. Clinical data from 1557 patients operated on for stage III gastric cancer according to the 7th edition between 2007 and 2014 were analyzed and compared using the 7th and 8th TNM classifications. A proposed staging system was established, and the three systems were compared in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…However, their conclusion that the 8th TNM edition may not provide better accuracy in predicting the prognosis of stage III gastric cancer is opposite to the findings of the present study. This also suggested a controversy regarding the superiority of the 8th edition and a large-scale, well-designed study is required to further confirm the conclusions, until which time retrospective analyses from different centers, including the present study, may provide insights into this issue (7)(8)(9). In the present study, the suitability of these modifications in the latest 8th edition TNM staging system were evaluated.…”
Section: Discussionmentioning
confidence: 67%
“…However, their conclusion that the 8th TNM edition may not provide better accuracy in predicting the prognosis of stage III gastric cancer is opposite to the findings of the present study. This also suggested a controversy regarding the superiority of the 8th edition and a large-scale, well-designed study is required to further confirm the conclusions, until which time retrospective analyses from different centers, including the present study, may provide insights into this issue (7)(8)(9). In the present study, the suitability of these modifications in the latest 8th edition TNM staging system were evaluated.…”
Section: Discussionmentioning
confidence: 67%
“…The placement of some pN3a patients was revised into stage IIIB, and pT3-4bN3bM0 was classified as stage IIIC [12]. Although previous studies have confirmed the prognostic value of the 8th AJCC stage system for gastric cancer (GC), it is mostly confined to patients with stage III [31], lymph node negative or lymph node the 15-Lymph Node Minimum [32,33]. Our study firstly evaluated the prognostic value of the 8th AJCC stage system for resectable GC from multicenter database.…”
Section: Discussionmentioning
confidence: 99%
“…The TNM system is widely used to offer guidance for the treatment of gastric cancer (7). The 8th edition of the TNM staging system for gastric cancer was released in 2016, replacing the 2009 7th edition (8). Compared with the previous edition, the 8th edition has no changes in the definition of T and N classifications.…”
Section: Discussionmentioning
confidence: 99%
“…The 8th edition of the tumor-node-metastasis (TNM) staging system (5), established by the American Joint Committee on Cancer and the Union for International Cancer Control (UICC), is the most commonly used system for predicting the prognosis of gastric cancer (6). The 8th edition TNM staging system is considered to be an objective and reliable method for predicting the prognosis of patients with gastric cancer (7), however, the requirement of at least 15 retrieved lymph nodes (LNs) limits the use of this system in clinical practice (8). Furthermore, stage migration may occur if a low number of LNs are retrieved, which may underestimate the severity of the disease (9).…”
Section: Introductionmentioning
confidence: 99%